The role of mtDAMPs in the trauma-induced systemic inflammatory response syndrome - Ye, Jingjing; Hu, Xiaodan; Wang, Zhiwei; Li, Rui; Gan, Lebin; Zhang, Mengwei; Wang, Tianbing (Frontiers in Immunology, 2023)
Systemic inflammatory response syndrome (SIRS) is a non-specific exaggerated defense response caused by infectious or non-infectious stressors such as trauma, burn, surgery, ischemia and reperfusion, malignancy, and others that can eventually lead to an uncontrolled inflammatory response. In addition to the early mortality due to the "first hits" after trauma, the trauma-induced SIRS and multiple organ dysfunction syndrome (MODS) are the main reasons for the poor prognosis of trauma patients as "second hits". Unlike infection-induced SIRS caused by pathogen-associated molecular patterns (PAMPs), trauma-induced SIRS is mainly mediated by damage-associated molecular patterns (DAMPs) including mitochondrial DAMPs (mtDAMPs).MtDAMPs released after trauma-induced mitochondrial injury, including mitochondrial DNA (mtDNA) and mitochondrial formyl peptides (mtFPs), can activate inflammatory response through multiple inflammatory signaling pathways. This review summarises the role and mechanism of mtDAMPs in the occurrence and development of trauma-induced SIRS.